Bone repair hydrogel as well as preparation method and application thereof

The bone repair hydrogel was prepared by cross-linking and curing of graphene derivative nanoparticles modified with double bond monomer modified biomacromolecular materials, which solved the problem of poor mechanical properties of traditional hydrogels, and achieved rapid and effective repair of bone defects and synergistic effects of the neurovascular system.

CN119587748APending Publication Date: 2025-03-11INST OF BIOLOGICAL & MEDICAL ENG GUANGDONG ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411926607.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-11

Smart Images

  • Figure CN119587748A_ABST
    Figure CN119587748A_ABST
Patent Text Reader

Abstract

The invention discloses bone repair hydrogel as well as a preparation method and application thereof. The bone repair hydrogel comprises hydrogel and silicate modified graphene derivative nanoparticles, the silicate modified graphene derivative nano particles are doped in the hydrogel; a precursor of the hydrogel is a double-bond monomer modified biological macromolecular material. Active element ions and silicon ions released by the silicate modified graphene derivative can enhance the synergistic effect of a neurovascular system by adjusting the expression of neurotrophic factors, angiogenesis factors and bone formation related proteins, so that the bone defect repair effect is enhanced. The graphene derivative nanoparticles can promote proliferation and differentiation of nerve cells, and can provide a good surrounding electrophysiological microenvironment for bone cells. According to the invention, inorganic particles and organic materials are combined and cross-linked to form a hydrogel network structure, so that various properties of the hydrogel are synergistically enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical materials, and specifically relates to a bone repair hydrogel and a preparation method and application thereof. Background Art

[0002] Large bone defects formed after trauma, tumor resection, car accidents, comminuted fractures, failed deformity correction or removal of infectious lesions often exceed the critical size of bone tissue self-repair, and their clinical treatment remains a challenge for orthopedic surgeons. For bone defects of critical size, many experts and scholars believe that it may be because the surrounding nerves and vascular tissues are also heavily damaged and cannot be effectively restored and regenerated.

[0003] Studies have shown that silicate-based biomaterials such as bioactive glass and bioactive ceramics have good osteogenic properties and can be doped with active element ions to further promote the regeneration of new bones. However, bioceramics generally degrade slowly and cannot quickly and effectively restore and regenerate bone defects. In addition, since there are natural electrical signals in tissues such as bones and nerves, and the conductivity of pure silicate materials is weak, it is impossible to provide a good surrounding electrophysiological microenvironment for bone cells. Hydrogel is a polymer with a cross-linked three-dimensional network structure that has hydrophilic groups and can swell in water but is insoluble in water. It is an important functional polymer material that can be used in electronics, medicine, cosmetics and other fields. It has many functions such as conductivity, drug loading, and repair. It is one of the current research hotspots in materials science. However, traditional degradable natural polymer hydrogels have poor mechanical properties and are difficult to be used in the fields of electronic skin and bone repair. Therefore, preparing a degradable hydrogel material that can promote the restoration of peripheral nervous system control, vascular regeneration, and thus promote bone defect repair, and has good conductivity is a technical problem that needs to be solved in this field. Summary of the invention

[0004] In order to overcome the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide a bone repair hydrogel. The second purpose of the present invention is to provide a method for preparing the above-mentioned bone repair hydrogel. The third purpose of the present invention is to provide an application of the above-mentioned bone repair hydrogel.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] The first aspect of the present invention provides a bone repair hydrogel, comprising a hydrogel and silicate-modified graphene derivative nanoparticles; the silicate-modified graphene derivative nanoparticles are doped in the hydrogel; and the precursor of the hydrogel is a biomacromolecule material modified by a double-bond monomer.

[0007] Preferably, the double-bond monomer in the double-bond monomer-modified biomacromolecule material is selected from at least one of methacrylic anhydride, methacrylic acid, and glycidyl methacrylate.

[0008] Preferably, the biomacromolecule material in the biomacromolecule material modified by the double-bond monomer is selected from at least one of collagen, gelatin, chitosan, sodium alginate and hyaluronic acid.

[0009] Preferably, the silicate in the silicate-modified graphene derivative nanoparticles is a salt composed of silicate ions and one or more metal ions; the metal element of the metal ions is selected from calcium, zinc, magnesium, strontium, iron or copper.

[0010] Preferably, the graphene derivative in the silicate-modified graphene derivative nanoparticles is selected from at least one of graphene oxide, reduced graphene oxide, fluorinated graphene, sulfidized graphene and boronized graphene.

[0011] Preferably, the silicate-modified graphene derivative nanoparticles are obtained by a preparation method comprising the following steps: a metal ion compound, a silane coupling agent and a graphene derivative are reacted to obtain the silicate-modified graphene derivative.

[0012] More preferably, the silane coupling agent is selected from at least one of tetraethoxysilane, methyltriethoxysilane, phenyltriethoxysilane, tetramethoxysilane, trimethoxysilane, dimethyldiethoxysilane and 3-aminopropyltriethoxysilane.

[0013] More preferably, the mass ratio of the active element-containing compound, the silane coupling agent and the graphene derivative is (0.1-0.7):(0.05-0.5):1.

[0014] More preferably, the preparation conditions of the silicate-modified graphene derivative nanoparticles are selected from one or more of the following:

[0015] a) the reaction time is 1-10h;

[0016] b) the reaction temperature is 60-300°C;

[0017] c) The reaction is carried out in water.

[0018] Further preferably, the method for preparing the silicate-modified graphene derivative nanoparticles also includes: adding the graphene derivative aqueous dispersion to the metal ion compound aqueous solution, mixing and adjusting the pH to 5-10; then adding a silane coupling agent, mixing and adjusting the pH to 4-9, and obtaining the silicate-modified graphene derivative by reacting the metal ion compound, the silane coupling agent and the graphene derivative in water.

[0019] More preferably, the reaction time is 2-8 hours.

[0020] More preferably, the reaction temperature is 150-200°C.

[0021] The second aspect of the present invention provides a method for preparing the bone repair hydrogel of the first aspect, comprising the following steps: mixing the silicate-modified graphene derivative, the double-bond monomer-modified biomacromolecule material, and the photoinitiator, and performing a photo-crosslinking and curing reaction to obtain the bone repair hydrogel.

[0022] Preferably, the curing reaction time is 10 to 60 seconds.

[0023] Preferably, the curing reaction is performed using blue light.

[0024] Preferably, the curing reaction temperature is 20 to 60°C

[0025] Preferably, the photoinitiator includes a cleavage-type photoinitiator and a hydrogen abstraction-type photoinitiator.

[0026] More preferably, the photoinitiator is selected from at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP), 2-hydroxy-1-[4-(hydroxyethoxy)-phenyl]-2-methyl-1-propanone, 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (Irgacure 2959).

[0027] Preferably, the method further comprises the following steps: dispersing the silicate-modified graphene derivative, the double-bond monomer-modified biomacromolecule material, and the photoinitiator in water or PBS buffer to prepare a solution / dispersion, and then mixing the solutions and / or dispersions to perform a photo-crosslinking and curing reaction to obtain the bone repair hydrogel.

[0028] More preferably, the concentration (w / v) of the silicate-modified graphene derivative dispersion is 0.005% to 30%, further preferably 0.01% to 20%, such as 10%.

[0029] More preferably, the concentration (w / v) of the double-bond monomer-modified biomacromolecule material solution is 2% to 12%, and further preferably 5% to 10%.

[0030] More preferably, the concentration (w / v) of the photoinitiator solution is 0.1% to 1%, and further preferably 0.1% to 0.5%.

[0031] More preferably, 8 to 12 parts by volume of a double-bond monomer-modified macromolecular material solution, 3 to 7 parts by volume of an initiator solution, 1 to 15 parts by volume of a silicate-modified graphene derivative dispersion and 2 to 6 parts by volume of water or PBS are mixed to undergo a cross-linking and curing reaction to obtain the bone repair hydrogel.

[0032] More preferably, the solutions and / or dispersions are mixed, and the final concentration of the silicate-modified graphene derivative nanoparticles is (0.01-100) mg / mL.

[0033] The third aspect of the present invention provides use of the bone repair hydrogel described in the first aspect in the preparation of a product that promotes bone repair.

[0034] Preferably, the medical material is a medical material that promotes wound surface and / or tissue repair, or a medical dressing that promotes wound surface and / or tissue regeneration.

[0035] The beneficial effects of the present invention are:

[0036] The present invention provides a bone repair hydrogel, which is a gel network structure obtained by cross-linking and curing a silicate-modified graphene derivative and a double-bond monomer-modified biomacromolecule material. Among them, the silicate-modified graphene derivative has multiple functions, and the released active element ions and silicon ions can enhance the synergistic effect of the neurovascular system by regulating the expression of neurotrophic factors, angiogenic factors and bone formation-related proteins, thereby enhancing the repair effect of bone defects. Graphene derivative nanoparticles have good affinity for nerve cells, can promote the proliferation and differentiation of nerve cells, and can provide a good surrounding electrophysiological microenvironment for bone cells, more reasonably meeting the multiple needs of bone defect repair and regeneration. In addition, the present invention uses a double-bond monomer-modified biomacromolecule material as a matrix material, such as methacrylated gelatin (GelMA), which has good cell adhesion and biocompatibility. The present invention combines inorganic particles with organic materials to form a hydrogel network structure, which synergistically enhances the various properties of the hydrogel, gives the hydrogel good biocompatibility and degradability, improves the mechanical strength of the overall material, and can more effectively perform neurovascular bone repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 XRD patterns of ZS-rGO and rGO powders;

[0038] Figure 2 SEM images of ZS-rGO and rGO powders;

[0039] Figure 3 Energy spectra of ZS-rGO (a) and rGO powder (b);

[0040] Figure 4 XRD patterns of GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels;

[0041] Figure 5 SEM images of GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels;

[0042] Figure 6 Compression curves of GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels;

[0043] Figure 7 is the electrical conductivity of GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels;

[0044] Figure 8 Degradation experimental diagrams of GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels;

[0045] Fig. 9 Silicon ion release diagram of GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels;

[0046] Fig.10 The zinc ion release graphs of GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels;

[0047] Fig.11 The results of cell proliferation experiments of GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels are shown;

[0048] Fig.12 The experimental diagram of osteogenesis-related gene expression of GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels;

[0049] Fig.13 This is the experimental diagram of angiogenesis-related gene expression in GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels. DETAILED DESCRIPTION

[0050] The present invention is further described in detail below through specific examples. The raw materials used in the following examples, unless otherwise specified, can be obtained from conventional commercial sources or prepared and separated by simple synthesis; the processes used, unless otherwise specified, are conventional processes in the art.

[0051] Example 1

[0052] This embodiment provides a bone repair hydrogel, and the preparation method thereof is as follows:

[0053] Zinc silicate modified reduced graphene oxide (ZS-rGO) was added to PBS at a concentration of 0.1% (w / v), and ultrasonicated for 60 minutes to make it uniformly dispersed to prepare solution A. A certain amount of GelMA (60% substitution degree) was weighed and dissolved in PBS at a concentration of 10% (w / v), and placed in a 50°C water bath to dissolve to prepare solution B. LAP was completely dissolved in PBS at a concentration of 2.5% (w / v) to prepare solution C. 100μL of solution A, 500μL of solution B, and 100μL of solution C were taken with 300μL PBS, and after thorough mixing, the final concentration of GelMA was 5%, the final concentration of LAP was 0.25%, and the concentration of ZS-rGO was 0.1mg / mL. It was added to the mold and UV crosslinked for 30s to solidify and form to obtain a bone repair hydrogel, labeled as GelMA / ZS-rGO.

[0054] Among them, the preparation method of ZS-rGO is as follows:

[0055] Disperse 150 mg of graphene oxide (GO) in 30 mL of ultrapure water for 1 hour to prepare liquid A. Dissolve 75 mg of zinc nitrate (Zn(NO3)2·6H2O) in 25 mL of ultrapure water to prepare liquid B. Add liquid A to liquid B while stirring, adjust pH to 8, stir magnetically for 1 hour, and mix thoroughly. Take 29 μL of tetraethoxysilane (density: 0.93 g / cm 3 ), added dropwise to the mixed solution, adjusted to pH = 7, magnetically stirred for 1 h, and then transferred into a hydrothermal reactor, reacted at 200 ° C for 5 h, the product was washed three times with ultrapure water and anhydrous ethanol, dried, and ground for later use.

[0056] Example 2

[0057] This embodiment provides a bone repair hydrogel, and the preparation method thereof is as follows:

[0058] Zinc silicate modified reduced graphene oxide (ZS-rGO) was added to PBS at a concentration of 0.1% (w / v), and ultrasonicated for 60 minutes to make it uniformly dispersed to prepare solution A. A certain amount of methacrylic anhydride modified chitosan (40% substitution degree) was weighed and dissolved in PBS at a concentration of 4% (w / v), and placed in a water bath at 20°C to dissolve to prepare solution B. LAP was completely dissolved in PBS at a concentration of 2.5% (w / v) to prepare solution C. 100μL of solution A, 500μL of solution B, and 100μL of solution C were taken with 300μL PBS, and after thorough mixing, the final concentration of photosensitive chitosan was 2%, the final concentration of LAP was 0.25%, and the concentration of ZS-rGO was 0.1mg / mL. It was added to the mold and UV cross-linked for 20s to solidify and form a bone repair hydrogel.

[0059] Among them, the preparation method of ZS-rGO is as follows:

[0060] Disperse 150 mg of graphene oxide (GO) in 30 mL of ultrapure water for 1 hour to prepare liquid A. Dissolve 35 mg of zinc chloride in 25 mL of ultrapure water to prepare liquid B. Add liquid A to liquid B under stirring, adjust pH to 8, stir magnetically for 1 hour, and mix thoroughly. Take 29 μL of tetraethoxysilane (density: 0.93 g / cm 3 ), added dropwise to the mixed solution, adjusted to pH = 7, magnetically stirred for 1 hour, and then transferred into a hydrothermal reactor, reacted at 200°C for 4 hours, the product was washed three times with ultrapure water and anhydrous ethanol, dried, and ground for later use.

[0061] Example 3

[0062] This embodiment provides a bone repair hydrogel, and the preparation method thereof is as follows:

[0063] The magnesium silicate modified reduced graphene oxide was added to PBS at a concentration of 1% (w / v), and ultrasonicated for 60 minutes to make it uniformly dispersed to prepare solution A. A certain amount of methacrylate glycidyl modified collagen (20% substitution degree) was weighed and dissolved in PBS at a concentration of 1.25% (w / v), and placed in a 20°C water bath to dissolve to prepare solution B. LAP was completely dissolved in PBS at a concentration of 2.5% (w / v) to prepare solution C (2.5% LAP). 100μL of solution A, 480μL of solution B and 100μL of solution C were mixed with 320μL PBS, and the final concentration of photosensitive collagen was 0.6%, the final concentration of LAP was 0.25%, and the concentration of magnesium silicate modified reduced graphene oxide was 1mg / mL. It was added to the mold and UV crosslinked for 50s to solidify and form a bone repair hydrogel.

[0064] Wherein, the preparation method of magnesium silicate modified reduced graphene oxide is as follows:

[0065] Disperse 150 mg of graphene oxide (GO) in 30 mL of ultrapure water for 1 hour to prepare liquid A. Dissolve 60 mg of magnesium sulfate in 25 mL of ultrapure water to prepare liquid B. Add liquid A to liquid B under stirring, adjust pH to 8, stir magnetically for 1 hour, and mix thoroughly. Take 58 μL of tetraethoxysilane (density: 0.93 g / cm 3 ), added dropwise to the mixed solution, adjusted to pH = 9, magnetically stirred for 1 hour, and then transferred into a hydrothermal reactor, reacted at 180°C for 6 hours, the product was washed three times with ultrapure water and anhydrous ethanol, dried, and ground for later use.

[0066] Example 4

[0067] This embodiment provides a bone repair hydrogel, and the preparation method thereof is as follows:

[0068] The copper silicate modified graphene sulfide was added to pure water at a concentration of 2% (w / v), and ultrasonicated for 60 minutes to make it uniformly dispersed to prepare solution A. A certain amount of methacrylic anhydride modified sodium alginate (35% substitution degree) was weighed and dissolved in pure water at a concentration of 3% (w / v), and placed in a water bath at 20°C to dissolve to prepare solution B. LAP was completely dissolved in pure water at a concentration of 2.5% (w / v) to prepare solution C (2.5% LAP). 100μL of solution A, 500μL of solution B and 160μL of solution C were mixed with 240μL of pure water, and the final concentration of photosensitive sodium alginate was 1.5%, the final concentration of LAP was 0.4%, and the concentration of copper silicate modified graphene sulfide was 2mg / mL. It was added to the mold and UV cross-linked for 60s to solidify and form a bone repair hydrogel.

[0069] Wherein, the preparation method of magnesium silicate modified reduced graphene oxide is as follows:

[0070] Disperse 150 mg of graphene sulfide (GO) in 30 mL of ultrapure water for 1 hour to prepare liquid A. Dissolve 60 mg of copper acetate in 25 mL of ultrapure water to prepare liquid B. Add liquid A to liquid B under stirring, adjust pH to 8, stir magnetically for 1 hour, and mix thoroughly. Take 58 μL of dimethyldiethoxysilane (density: 0.93 g / cm 3 ), added dropwise to the mixed solution, adjusted to pH = 6.5, magnetically stirred for 1 h, and then transferred into a hydrothermal reactor, reacted at 220 ° C for 3 h, the product was washed three times with ultrapure water and anhydrous ethanol, dried, and ground for later use.

[0071] Comparative Example 1

[0072] In this comparative example, a hydrogel with a final rGO concentration of 0.1 mg / mL was prepared. The difference from Example 1 was that reduced graphene oxide (rGO) was used to replace ZS-rGO in equal amounts. The specific preparation process was consistent with the preparation method in Example 1, and the obtained hydrogel was labeled as GelMA / rGO.

[0073] The preparation method of rGO is as follows:

[0074] 150 mg of graphene oxide (GO) was dispersed in 30 mL of ultrapure water for 1 h, the pH was adjusted to 7, magnetic stirring was performed for 1 h, and then transferred into a hydrothermal reactor and reacted at 200 °C for 5 h. The product was washed three times with ultrapure water and anhydrous ethanol, dried, and ground for later use.

[0075] Comparative Example 2

[0076] In this comparative example, a hydrogel with a final ZS-rGO concentration of 0% was prepared. The difference from Example 1 is that ZS-rGO was not used. The specific preparation process was consistent with the preparation method in Example 1, and the obtained hydrogel was marked as GelMA.

[0077] Experimental analysis

[0078] This test example tests the properties of the hydrogels prepared in the examples and comparative examples and the properties of the nanoparticle powders ZS-rGO and rGO.

[0079] 1. Use X-ray diffractometer (XRD) to test ZS-rGO and rGO powders. The test results are as follows: Figure 1 As shown. A broad peak appears at 2θ=8° for GO and around 2θ=24° for rGO, corresponding to the characteristic diffraction peak of the (002) crystal plane. This shows that after reduction, the graphene interlayer spacing has increased and the layered structure has become disordered. Compared with rGO, the XRD spectrum of ZS-rGO not only still has a broad peak near 24°, but also has several weaker diffraction peaks between 2θ=20-25°, corresponding to the related crystal planes of ZnO and SiO2. Some sharp peaks appear at 2θ angles such as 30-40°, 56°, and 62°, which are attributed to the characteristic crystal planes of ZnO. A weak peak appears at around 15°, which is attributed to the diffraction signal of bonding structures such as Zn-O-Si. These additional characteristic diffraction peaks indicate that inorganic components such as ZS have been successfully introduced on the surface of rGO to form ZS-rGO.

[0080] Figure 2 SEM images of ZS-rGO and rGO powders; Figure 3 Energy spectra of ZS-rGO (a) and rGO powder (b); Figure 2 and Figure 3 It can also be verified that inorganic components such as ZS were successfully introduced on the surface of rGO to form ZS-rGO

[0081] 2. Bone repair hydrogel

[0082] (1) Composition and morphology characterization

[0083] X-ray diffractometer (XRD) was used to test GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels. The ultra-energy detection counter records the diffraction intensity curve between 2θ=5° and 90°, and the scanning speed is 5° / min. Figure 4 The XRD spectra of the three groups show that the spectra are relatively similar, and the mantou peak of the diffraction peak curve appears at about 20-23°, indicating that they are amorphous, indicating that the addition of ZS-rGO has little effect on the composition of the hydrogel.

[0084] Scanning electron microscopy (SEM) was used to analyze the morphology of GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels. The prepared GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogel samples were freeze-dried and then fractured in liquid nitrogen. After the cross-section was gold-sprayed, the morphology and microstructure of the sputtered gold samples were tested using a scanning electron microscope (SEM). The test results are shown in the figure. Figure 5 shown. Figure 5 It shows that the surfaces of the three groups of hydrogels, GelMA, GelMA / rGO, and GelMA / ZS-rGO, all have porous structures, and there is no significant difference in the pore sizes.

[0085] (2) Mechanical properties

[0086] The mechanical properties of GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels were tested using a mechanical testing machine. The three groups of hydrogels after light curing were demoulded and subjected to compression tests on the mechanical testing machine to test the mechanical properties of the three groups of hydrogels. The diameter of the scaffold was about 6 to 8 mm, and the height was 4 to 6 mm. The test setting was 2 mm / min. The test results are shown in the figure. Figure 6 shown.

[0087] Figure 6 The compression curves of GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels were shown. The mechanical properties of the GelMA group were the worst, but after the addition of rGO, the mechanical properties of its hydrogel were enhanced compared with the GelMA group. After the addition of ZS-rGO, the mechanical properties were further enhanced compared with GelMA / rGO, and under the same compression displacement, the GelMA / ZS-rGO hydrogel group performed the best, indicating that it can respond to mechanical compression faster and continuously enhance mechanical strength. This shows that silicate-modified graphene derivatives are beneficial to improving the mechanical properties of hydrogels.

[0088] (3) Conductive properties

[0089] Three groups of hydrogels, GelMA, GelMA-rGO, and GelMA / ZS-rGO, were prepared, and the conductivity of the three groups of composite hydrogels was tested using an electrochemical workstation. The three groups of composite hydrogel samples were discs with a diameter of 2 cm. Platinum electrodes were attached to both ends, and the resistance was calculated using the current-time curve. The conductivity was calculated according to the following formula: R = U / I; σ = L / R×S. Where: R is the resistance, in Ω; U is the open circuit potential of the conductive hydrogel, in V; I is the current corresponding to the open circuit potential, in A. σ is the conductivity, in S / m; L is the distance between the two electrodes, in m; S is the cross-sectional area of ​​the measured hydrogel, m 2 . Figure 7 The results showed that after adding rGO and ZS-rGO, the conductivity of GelMA / rGO and GelMA / ZS-rGO hydrogels was significantly improved compared with pure GelMA gel.

[0090] (4) Degradation and ion controlled release

[0091] Three groups of hydrogels, GelMA, GelMA-rGO, and GelMA / ZS-rGO, were prepared. The volume of each sample was 300 μL. 2 mL of PBS solution was added to each sample. The solution was changed every 7 days. The time points for solution and sampling were 1d, 3d, 1W, 2W, 3W, and 4W. The samples were taken out at specific time points and washed 3 times with deionized water (if there are fragments, they should be filtered, washed, and collected). After the samples and fragments were freeze-dried, the mass Wd of the different samples after degradation was weighed and recorded, and the degradation rate was calculated. The degradation rate of different samples was calculated according to the following formula (n=4). Degradation rate (%) = (W0-Wd) × 100% / W0, Wd is the mass of the sample on each day, and W0 is the original dry mass of the sample. After 4W of degradation, Figure 6 The results showed that the hydrogels in the GelMA-rGO and GelMA / ZS-rGO groups degraded more slowly than those in the GelMA group, indicating that the introduction of ZS-rGO and rGO can effectively delay the degradation of pure biomacromolecule materials, and can better match the bone repair process in vivo with the material degradation rate, so that bone tissue can grow in an orderly manner and gradually restore the original structure.

[0092] Three groups of hydrogels, GelMA, GelMA-rGO, and GelMA / ZS-rGO, were prepared. The volume of each sample was 300 μL, and the three groups of composite hydrogels were subjected to ion release experiments. The samples were added to a centrifuge tube, soaked with 2 mL of PBS, and placed in a constant temperature oscillator at 37 ° C. The supernatant was collected at different time points (1, 3d, 7d, 14d, 21d, and 28d), and an equal volume of PBS was added. The concentration of Zn and Si ions in the supernatant was detected by inductively coupled plasma emission spectrometry (ICP), and the release of silicon ions and zinc ions with the change of days was detected. Fig. 9 and Fig.10 The results showed that both silicon ions and zinc ions can be continuously released over the days, which is beneficial for the continued role of silicon ions and zinc ions in the bone repair process in vivo.

[0093] (5) Cytocompatibility

[0094] The cell compatibility of GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels was tested. Bone marrow mesenchymal stem cells were implanted on the three groups of hydrogels to detect their proliferation. The test results are as follows: Fig.11 shown. Fig.11 The cell proliferation experiment showed that GelMA, GelMA / rGO and GelMA / ZS-rGO hydrogels all had good cell compatibility. The cell compatibility of GelMA / ZS-rGO was significantly better than that of GelMA hydrogel, and it was also better than that of GelMA / rGO hydrogel.

[0095] (6) Evaluation of in vitro osteogenic, angiogenic, and neurogenic properties

[0096] Rat bone marrow mesenchymal stem cells (BMSCs) were implanted on GelMA, GelMA / rGO, and GelMA / ZS-rGO hydrogels, respectively. After co-culture of BMSCs with the three groups of gels for 14 days, the expressions of representative bone repair-related marker genes, such as osteogenesis-related genes (ALP, Col-1, OCN, OPN, RunX-2, and BMP2), angiogenesis-related genes (VEGF), and neurogenic genes (MAP-2 and TB-3), were detected by real-time RT-qPCR using the Quantitect SYBRGreen PCR kit according to the instructions of the kit. The effects of the composite gel on the osteogenesis, angiogenesis, and neurogenic properties of cells were evaluated. The results are shown in Table 1. Fig.12 and Fig.13After 14 days of culture, compared with the GelMA group, the GelMA / ZS-rGO group had significantly higher or higher expression of bone-related genes (ALP, Col-1, OCN, RunX-2 and BMP2), angiogenic genes (VEGF) and neurogenic genes (MAP-2). These results indicate that the GelMA / ZS-rGO hydrogel can meet the requirements of neurovascularized bone repair.

[0097] In summary, GelMA / ZS-rGO hydrogel has excellent cytocompatibility, mechanical properties, and good rheological and swelling properties, and can be used for neurovascularized bone repair.

[0098] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A bone repair hydrogel, characterized in that: It comprises hydrogel and silicate-modified graphene derivative nanoparticles; the silicate-modified graphene derivative nanoparticles are doped in the hydrogel; and the precursor of the hydrogel is a biomacromolecule material modified by a double-bond monomer.

2. The bone repair hydrogel according to claim 1, characterized in that: The double-bond monomer in the biomacromolecule material modified with the double-bond monomer is selected from at least one of methacrylic anhydride, methacrylic acid, and glycidyl methacrylate; And / or, the biomacromolecule material in the biomacromolecule material modified by the double-bond monomer is selected from at least one of collagen, gelatin, chitosan, sodium alginate and hyaluronic acid.

3. The bone repair hydrogel according to claim 1, characterized in that: The silicate in the silicate-modified graphene derivative nanoparticles is a salt composed of silicate ions and one or more metal ions; the metal element of the metal ions is selected from calcium, zinc, magnesium, strontium, iron or copper; And / or, the graphene derivative in the silicate-modified graphene derivative nanoparticles is selected from at least one of graphene oxide, reduced graphene oxide, fluorinated graphene, sulfidized graphene, and boronized graphene.

4. The bone repair hydrogel according to claim 3, characterized in that: The silicate-modified graphene derivative nanoparticles are prepared by a preparation method comprising the following steps: a metal ion compound, a silane coupling agent and a graphene derivative are reacted to obtain the silicate-modified graphene derivative.

5. The bone repair hydrogel according to claim 4, characterized in that: The silane coupling agent is selected from at least one of tetraethoxysilane, methyltriethoxysilane, phenyltriethoxysilane, tetramethoxysilane, trimethoxysilane, dimethyldiethoxysilane and 3-aminopropyltriethoxysilane; And / or, the mass ratio of the active element-containing compound, the silane coupling agent and the graphene derivative is (0.1-0.7):(0.05-0.5):

1.

6. The bone repair hydrogel according to claim 4, characterized in that: The preparation conditions of the silicate-modified graphene derivative nanoparticles are selected from one or more of the following: a) the reaction time is 1-10h; b) the reaction temperature is 60-300°C; c) The reaction is carried out in water.

7. The method for preparing the bone repair hydrogel according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing the silicate-modified graphene derivative, the double-bond monomer-modified biomacromolecule material and the photoinitiator, and performing a light-irradiation cross-linking and curing reaction to obtain the bone repair hydrogel.

8. The method for preparing the bone repair hydrogel according to claim 1, characterized in that: The method also includes the following steps: dispersing the silicate-modified graphene derivative, the double-bond monomer-modified biomacromolecule material, and the photoinitiator in water or PBS buffer to prepare a solution / dispersion liquid, and then mixing the solutions and / or dispersion liquids to perform a light cross-linking and curing reaction to obtain the bone repair hydrogel.

9. The method for preparing the bone repair hydrogel according to claim 7, characterized in that: The curing reaction time is 10 to 60 seconds.

10. Use of the bone repair hydrogel according to any one of claims 1 to 6 in the preparation of a product for promoting bone repair.